2000
DOI: 10.1097/00005392-200009020-00017
|View full text |Cite
|
Sign up to set email alerts
|

Histology of the Urethral Plate: Implications for Hypospadias Repair

Abstract: The urethral plate consists of epithelium overlying connective tissue. We found no histological evidence of fibrous cords historically considered responsible for chordee.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
36
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 6 publications
5
36
0
1
Order By: Relevance
“…Interestingly, an intraoperative biopsy of the urethral plate in the boy with subsequent neourethral contracture showed healthy connective tissue histologically indistinguishable from that of other patients who had no complications. There was no evidence of dysplasia or ®brosis of the urethral plate, which supports our previous conclusion that the plate is comprised of wellvascularized tissues [9], and the different appearance after its incision in both cases was thought to result from de®ciency of otherwise unremarkable connective tissue.…”
Section: Discussionsupporting
confidence: 86%
“…Interestingly, an intraoperative biopsy of the urethral plate in the boy with subsequent neourethral contracture showed healthy connective tissue histologically indistinguishable from that of other patients who had no complications. There was no evidence of dysplasia or ®brosis of the urethral plate, which supports our previous conclusion that the plate is comprised of wellvascularized tissues [9], and the different appearance after its incision in both cases was thought to result from de®ciency of otherwise unremarkable connective tissue.…”
Section: Discussionsupporting
confidence: 86%
“…Epithelialization probably occurs from the edges to the center, forming a 'carpet' of cells on the tunica albuginea that proliferate to form the new epithelium; this is similar to what occurs in the TIP technique, as previously experimentally demonstrated [24][25][26]. It seems that Group 1 behaved like an extended TIP, in that healing was similar, even without the urethral plate underlying tissue, which is rich in blood vessels and connective tissue [28,29].…”
Section: Discussionsupporting
confidence: 57%
“…[12] Historically, pres ervation of the urethral plate was thought to contrib ute to ventral penile curvature that often complicates hypospadias surgery. However, Snodgrass et al, histologically, found the urethral plate to consist of well vascularized connective tissue comprised of healthy appearing, smooth muscle and collagen with out any fibrous scar or dysplastic tissues [13] . Preserva tion of the urethral plate, which is a fixed structure, prevents formation of a baggy urethra and helps in propulsion of the urine without diverticulum forma tion.…”
Section: Discussionmentioning
confidence: 99%